PENGARUH PENGANGGARAN, PROSEDUR KALIBRASI, DAN PRAKTIK SUMBER DAYA MANUSIA TERHADAP KEPATUHAN PELAKSANAAN KALIBRASI ALAT KESEHATAN DI PUSKESMAS SE-KABUPATEN GUNUNGKIDUL - Endang Ertin Suprihatin (Program Magister Manajemen STIE Widya Wiwaha Yogyakarta, 2021)
This study aimed to analyze the effect of budgeting, calibration procedures, and human resource practices on compliance with health equipment calibration. This study used predictive quantitative research. The populations used in this study were 30 health centers in Gunung Kidul, Yogyakarta. The data was collected using questionnaire and analyzed using regression analysis. Before distributing questionnaire, we tested its validity and reliability. Based on the validity test, all items was valid. The reliability test indicated that the questionnaire was reliable. The results of this study showed that there was a significant effect between budgeting, calibration procedures, and human resource practices on compliance with calibration implementation.